EFEKTIVITAS METODE FIELD TRIP DALAM MENINGKATAN KEMAMPUAN MENULIS KARANGAN DESKRIPSI MURID SD - Nurhaedah Nurhaedah; Hamzah Pagarra (Universitas Negeri Makassar, 2017)
Effectiveness Field Trip methods in Improving the Descriptive Writing Ability of Elementary Pupils. This study aims at determining the effectiveness of learning methods in improving the writing ability of fifth grade students in Enrekang and to know the difference of learning outcomes by using trip method and conventional model. This research used quantitative approach through experimental method by using pretest-posttest control group design. The results showed that the Field Trip was effective in teaching descriptive writing of the fifth grade students at elementary school at Enrekang.